Some aspects regarding tourism and youth's mobility - Moisa, Claudia (Array, 2008)
Summary: To many countries of world, youth tourism represents the movement of the youth, that have a higher education, which represents an important income, source for that countries. Very important is the relationship between the tourism and various operational exchange programmes for students, as SOCRATES and ERASMUS for Europe or the European Community of West African States (ECOWAS) for intercultural exchanges between the students. Beginning from the Antiquity, wealthy young people had the privilege to discover the world and to aquisit new knowledge over practicing tourism abroad, the educational tourism being in the centre of the interest for the high society with high incomes. Since the end of the Second World War, a big number of politicians, more or less young, promoted the traveling idea as a factor of permanent education, and the governmental organizations with attributions in the field regarding the young people have promoted the young's mobility, first, at national level, the first mobility actions for young people of "Knowledge…" type being addressed to large number of people. In a short time, the governments of different countries have established protocols and bilateral accords within which lots of programs permitted to the young people, teachers, professors and animators to have abroad trips. In the last period, the most utilized concept is that of mobility, of intercultural learning, of recapture, of study traveling, all these referring to the young travelers, in this case supporting being essential, at national or at European level, which is exemplified by the professional level mobility or at educational level